2009
DOI: 10.1073/pnas.0902657106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a vesicle in general flow

Abstract: An approach to quantitatively study vesicle dynamics as well as biologically-related micro-objects in a fluid flow, which is based on the combination of a dynamical trap and a control parameter, the ratio of the vorticity to the strain rate, is suggested. The flow is continuously varied between rotational, shearing, and elongational in a microfluidic 4-roll mill device, the dynamical trap, that allows scanning of the entire phase diagram of motions, i.e., tank-treading (TT), tumbling (TU), and trembling (TR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(136 citation statements)
references
References 27 publications
7
128
0
1
Order By: Relevance
“…(4) becomes Jeffery's equation [62] for solid ellipsoidal objects, where φ is kept in the original position. These results show good agreement with recent experiments of lipid vesicles [7][8][9].…”
Section: A Fluid Vesiclesupporting
confidence: 93%
See 1 more Smart Citation
“…(4) becomes Jeffery's equation [62] for solid ellipsoidal objects, where φ is kept in the original position. These results show good agreement with recent experiments of lipid vesicles [7][8][9].…”
Section: A Fluid Vesiclesupporting
confidence: 93%
“…Recently, the dynamics of lipid vesicles in steady shear flow was intensively investigated [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A lipid vesicle can be considered as a microcapsule in the small limit of the shear modulus µ → 0.…”
Section: Introductionmentioning
confidence: 99%
“…see [11,28,53,16]. It has also been reported recently that a time-dependent flow with a switch in the direction of the velocity gradient can also lead to bud formation [6]. Here our flow field is far more complicated than the elongation flow.…”
Section: 3mentioning
confidence: 67%
“…Finken and Seifert [18] performed a mathematical analysis and derived analytical results both for the threshold value of the shear rate and for the critical wavelength of the wrinkling. Kantsler et al also found that vesicle wrinkling may occur in time-dependent elongation flow [19,6]. It has been suggested that the winkling phenomena are related to the dynamical instability induced by negative surface tension of the membrane [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation